PROSES MANUFAKTUR MESIN PEMERAS NIRA SORGUM TIGA ROLL - Alif Fayadhillah Azhar (2022)
Sorghum is a plant that has great potential to be cultivated in Indonesia. Sorghum is still in the same family as rice and maize, which are cereal crops. Sorghum is hardy to survive in dry areas and does not require a lot of water. Of the many parts of the sorghum plant that can be used, the stem is one part that can be used to extract the juice. With the rapid development of agriculture in Indonesia, the people's need for sugar has also increased. In this study, the authors designed a machine for squeezing sorghum juice. Squeezing machine is a machine used to squeeze plant stems using a squeeze roller to produce sap. The purpose of designing this squeezing machine is to increase production capacity and shorten production time in producing sorghum juice. The method used in carrying out this design begins with a literature study and field study, concept design, analyzing manufacturing processes and machinery, to testing the tool. This sorghum juice squeezer machine has dimensions of 50x34x37 for the machine. The engine frame has dimensions of 55x45x50. The main components of this machine include the engine frame, engine mount, squeeze roller, engine protector, juice container, and driving motor. This machine is driven by a 5.5 HP gasoline motor and the engine speed is channeled through a belt and pulley. This machine can squeeze sorghum as much as 401,516kg/hour.